Autopsy Death Profile Due to Railway Injury in Mangalore, A Coastal City of South Karnataka- A Retrospective Analysis - Ibrahim Jibril; B Suresh Kumar Shetty; Pavanchand Shetty; Jagadish Rao Padubidri; Haneil Larson D’souza; Eshetu Sileshi; Miressa Belay (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Accident deaths is one of the most common types of deaths in India. In India railway relateddeaths are reported throughout the year. Fatal trains impacts cause extensive musculoskeletal injuries due tothe nature of the object as well as the amount of force transmitted during impacts. The purpose of all accidentinvestigation to take a positive step in correction of causation and to prevent such incidents in the future.Objective: The aim of this study is to assess and learn demographic details, characteristics of the incident infatal train crashes and recognize the injury profile.Methods: This is a retrospective autopsy based study. We considered 59 cases of railway track relateddeaths in three years (2016-2018) conducted at Tertiary Care Hospital, mortuary, Mangalore and analyzedthem statistically.Results: The study showed most of the victims were men between 30-40 years of age. Most victims ofincidents were pedestrians (72.9%,). The circumstance of incident in the majority was while walking on sideof railway track (39%). The highest number of fatalities 42.4 % were observed between 6 Am to 12 pm.Analysis as to cause of death in accidental circumstances revealed that multiple injuries (35.9%) followedby blunt trauma of head (33.3%) and in suicidal circumstances, death due to blunt trauma to head (40%) anddecapitation (40%) were the most prevalent.Limitations: The study needs to be done for longer duration and more detailed parameters in the railwaytrack accidents.Conclusion: The study established that majority of railway related deaths are accidental. and there is arequirement of awareness and implementing strict traffic laws to strengthen their safety for such preventabledeaths especially among the commuters of train and among the pedestrians using railway level crossings